Migrant Deaths in the Arizona Desert : La vida no vale nada - Rubio-Goldsmith, Raquel; Masterson-Algar, Araceli; Finch, Jessie K.; Fernández, Celestino (Book collections on Project MUSE., 2016)
"Migrant Deaths in the Arizona Desert addresses the tragic results of government policies on immigration. The contributors consist of a multidisciplinary group who are dedicated to the thousands of men, women, and children who have lost their lives while crossing the desert in search of a better life. Each chapter in this important new volume seeks answers to migrant deaths, speaking to the complexity of this tragedy via a range of community and scholarly approaches"--Provided by publisher